Imiona nadawane dzieciom pozostawionym w Szpitalu Dzieciątka Jezus w Warszawie w 1870 roku – spojrzenie socjoonomastyczne - Kresa, Monika (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The article examines the names of 917 abandoned children at the Infant Jesus Hospital in Warsaw in 1870. A total of 123 female and 131 male names were analyzed for frequency, origin and motivation. The study tests J.S. Bystroń’s hypothesis that illegitimate children – who dominated in the orphanage – were given stigmatizing names. However, a comparison with names given to all children in Warsaw in 1870–1871 shows that this hypothesis lacks support. The naming patterns of abandoned children do not differ significantly from general naming trends. Minor differences are linked to the specific context of naming in the shelter. Some naming motivations were identified (e.g. the popularity of Anna), while others remain unclear (e.g. Onufry, given six times, yet absent elsewhere that year). The study also shows an effort to preserve ties to the mothers’ names when available. Notably, calendar-based naming played only a small role. Since the naming of abandoned children has received little attention in onomastic research, these archival records provide valuable insights and open new directions for study.